Про алгоритм квантизації типу Дірака для коливних динамічних систем Неймана - Боголюбова (Нелінійні коливання, 2001)
A Dirac type quantization algorithm is applied to the Neumann-Bogoliubov oscillatory dynamical system and the corresponding Heisenberg operator equations are derived